2008
DOI: 10.1590/s1678-91992008000200012
|View full text |Cite
|
Sign up to set email alerts
|

Anti-coagulase-negative Staphylococcus activity of ethanolic extracts of propolis from two Brazilian regions and synergism with antimicrobial drugs by the E-test method

Abstract: Propolis is a natural resinous substance collected by bees from vegetal sources and its therapeutic properties have been investigated. In this work, we evaluated the inhibitory activity of ethanolic extracts of propolis (EEP) from the Southeast and South of Brazil on coagulase-negative Staphylococcus (CNS) growth as well as the EEP in vitro synergism with antimicrobial drugs by using the diffusion method (E-test). The EEP chemical characteristics (dry weight, pH, flavonoid and phenolic compounds) were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Mantovani et al [46] demonstrated strong anti-CoNS activity of propolis. Najmadeen and Kakamand studies [47] on ethanol extracts of propolis activities on S. epidermidis and S. aureus showed that S. epidermidis strains were less susceptible to different propolis extracts than coagulase positive staphylococci.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mantovani et al [46] demonstrated strong anti-CoNS activity of propolis. Najmadeen and Kakamand studies [47] on ethanol extracts of propolis activities on S. epidermidis and S. aureus showed that S. epidermidis strains were less susceptible to different propolis extracts than coagulase positive staphylococci.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in this study all S. epidermidis strains MIC EEPP ranged from 0.2 to 0.39 mg/mL and from 0.39 to 0.78 mg/mL after 12 and 24 hours of incubation, respectively, which suggested that EEPP activity might diminish over time. The determination of the chemical characteristics of EEP showed that the phenolic compounds were mainly responsible for the anti-CoNS activity of EEP collected from the Southeast of Brazil [46]. The findings of another study, evaluating the antibacterial properties of extracts of propolis from Mexico, revealed that the highest sensitivity towards propolis was shown by S. aureus , S. epidermidis, and the two Vibrio cholerae strains with MICs values <0.125 mg/mL [49].…”
Section: Discussionmentioning
confidence: 99%
“…Colored zones produced on a pale background indicated positive result for detection of alcohols, phenols, and steroids compounds [7].…”
Section: Spraying Methodsmentioning
confidence: 99%
“…However, ethanolic extract and essential oil of propolis present different chemical compositions (20). Probably, diverse extraction procedures result in dissimilar chemical compounds, and ultimately, could contribute to differences in the antibacterial activities (29,30). It is not so clear whether the antibacterial effect may be caused by a single active component or by the synergy of many active constituents found in the essential oil.…”
Section: Antibacterial Activitymentioning
confidence: 99%